Large‐scale preparation of nano‐sized carbides and metal whiskers via mechanochemical decomposition of MAX phases. Issue 2 (28th August 2022) - Tian, Zhihua; Xu, Xueqin; Tang, Jingwen; Zhang, Qianqian; Wu, Fushuo; Zhang, Peigen; Liu, Jian; Sun, ZhengMing
Abstract: Nano‐sized transition metal carbide powder is usually synthesized by chemical methods such as chemical vapor deposition, while its large‐scale synthesis is a long‐standing challenge due to high energy consumption and low yield; metal nanowires (NWs) (mainly noble metals) are usually prepared by wet chemistry, and more compositions and greener preparation routes for metal NWs are urgent to meet the needs of the high technology industry. Herein, MAX phases are mechanochemically decomposed, resulting in the fine corresponding binary M‐X carbides and the A‐site metal whiskers. This implies a feasible top‐down route for efficiently preparing fine carbides and high‐quality metal whiskers on large scale. Several example MAX phases (both 312 and 211) are selected to demonstrate the feasibility of this method. The carbides and metal whiskers are characterized by X‐ray diffractometer, scanning electron microscope, transmission electron microscopy, and energy‐dispersive X‐ray spectroscopy to identify their morphology, composition, and phase. The compositional diversity of MAX phases bodes that this would be a promising alternative avenue to preparing various nano‐sized carbides and single‐crystal metal whiskers.